Laser coupling in waterjets subject to jet instabilities, laser parameters, and alignment errors - Wei, Meirong; Zhang, Tao; Liu, Yan; Wang, Ze; Dong, Zulin; Huang, Zixuan (Optics express, 2023)
High coupling accuracy and efficiency attract wide attention in waterjet-guided laser technology due to the requirements for high processing performance in hard-to-cut material and diamond industries. The behaviors of axisymmetric waterjets injected into the atmosphere through different types of orifices are investigated by adopting a two-phase flow k-epsilon algorithm. The water-gas interface is tracked with Coupled Level Set and Volume of Fluid method. The electric field distributions of laser radiation inside the coupling unit are modeled by wave equations and numerically solved with the full-wave Finite Element Method. The coupling efficiency of the laser beam affected by waterjet hydrodynamics is studied by considering the profiles of the waterjet shaped at transient stages, namely vena contracta, cavitation, and hydraulic flip. The growth of the cavity leads to a larger water-air interface and increases the coupling efficiency. Eventually, two types of fully developed laminar waterjets, i.e. constricted waterjets and non-constricted waterjets, are formed. Constricted waterjets that are detached from the wall throughout the nozzle are preferable to guide laser beams since they significantly increase the coupling efficiency compared to non-constricted waterjets. Furthermore, the trends of coupling efficiency affected by Numerical Aperture (NA), wavelengths, and alignments errors are analyzed to optimize the physical design of the coupling unit and develop the alignment strategies.